India in a reconnecting Eurasia : foreign economic and security interests - Sachdeva, Gulshan (Eurasia from the outside in., 2016)
"Examines the full scope of Indian national interests in the South Caucasus and Central Asia and analyzes the broad outlines of Indian engagement over the coming years"--Publisher's web site